Acvr1 deletion in osteoblasts impaired mandibular bone mass through compromised osteoblast differentiation and enhanced sRANKL‐induced osteoclastogenesis. Issue 6 (29th November 2020) - Hu, Yue; Hao, Xinqing; Liu, Cangwei; Ren, Chunxia; Wang, Shuangshuang; Yan, Guangxing; Meng, Yuan; Mishina, Yuji; Shi, Ce; Sun, Hongchen
Abstract: Bone morphogenetic protein (BMP) signaling is well known in bone homeostasis. However, the physiological effects of BMP signaling on mandibles are largely unknown, as the mandible has distinct functions and characteristics from other bones. In this study, we investigated the roles of BMP signaling in bone homeostasis of the mandibles by deleting BMP type I receptor Acvr1 in osteoblast lineage cells with Osterix ‐Cre. We found mandibular bone loss in conditional knockout mice at the ages of postnatal day 21 and 42 in an age‐dependent manner. The decreased bone mass was related to compromised osteoblast differentiation together with enhanced osteoclastogenesis, which was secondary to the changes in osteoblasts in vivo. In vitro study revealed that deletion of Acvr1 in the mandibular bone marrow stromal cells (BMSCs) significantly compromised osteoblast differentiation. When wild type bone marrow macrophages were cocultured with BMSCs lacking Acvr1 both directly and indirectly, both proliferation and differentiation of osteoclasts were induced as evidenced by an increase of multinucleated cells, compared with cocultured with control BMSCs. Furthermore, we demonstrated that the increased osteoclastogenesis in vitro was at least partially due to the secretion of soluble receptor activator of nuclear factor‐κB ligand (sRANKL), which is probably the reason for the mandibular bone loss in vivo. Overall, our results proposed that ACVR1 played essential roles in maintaining mandibular bone homeostasis through osteoblast differentiation and osteoblast‐osteoclast communication via sRANKL. Abstract : ACVR1 promotes osteoblastic differentiation and inhibits osteoclastogenesis through osteoblast‐osteoclast communication via sRANKL. ACVR1 plays an essential role in the maintenance of mandibular bone homeostasis.